Chronic psychosocial stress disturbs long-bone growth in adolescent mice - Sandra Foertsch (Disease Models & Mechanisms, 2017)
Although a strong association between psychiatric and somatic disorders is generally accepted, little is known regarding the interrelationship between mental and skeletal health. Although depressive disorders have been shown to be strongly associated with osteoporosis and increased fracture risk, evidence from post-traumatic stress disorder (PTSD) patients is less consistent. Therefore, the present study investigated the influence of chronic psychosocial stress on bone using a well-established murine model for PTSD. C57BL/6N mice (7 weeks old) were subjected to chronic subordinate colony housing (CSC) for 19 days, whereas control mice were singly housed. Anxiety-related behavior was assessed in the open-field/novel-object test, after which the mice were euthanized to assess endocrine and bone parameters. CSC mice exhibited increased anxiety-related behavior in the open-field/novel-object test, increased adrenal and decreased thymus weights, and unaffected plasma morning corticosterone. Microcomputed tomography and histomorphometrical analyses revealed significantly reduced tibia and femur lengths, increased growth-plate thickness and reduced mineral deposition at the growth plate, suggesting disturbed endochondral ossification during long-bone growth. This was associated with reduced Runx2 expression in hypertrophic chondrocytes in the growth plate. Trabecular thicknesses and bone mineral density were significantly increased in CSC compared to singly housed mice. Tyrosine hydroxylase expression was increased in bone marrow cells located at the growth plates of CSC mice, implying that local adrenergic signaling might be involved in the effects of CSC on the skeletal phenotype. In conclusion, chronic psychosocial stress negatively impacts endochondral ossification in the growth plate, affecting both longitudinal and appositional bone growth in adolescent mice.